A comparative study of mechanical, dynamic mechanical and morphological characterization of tampico and coir fibre-reinforced LLDPE processed by rotational moulding. Issue 1 (June 2022) - Abhilash, SS; Lenin Singaravelu, D
Natural fibres find their application as a reinforcing agent for polymer composites to obtain parts with improved mechanical properties. Manufacturing of non-metallic products is incorporated with natural fibres for better strength and to reduce cost. Rotational moulding is a process used for the manufacturing of hollow plastic products, especially water tanks, plastic fuel tanks, barrels, kayaks, refrigerated panels, etc. Incorporation of natural fibres to reinforce polymers in rotational moulding process is a tedious task; since there is no control over fibre and polymer powder mixture, which is rotating bi-axially, it may lead to fibre agglomeration. The present work investigates the mouldability of linear low density polyethylene composites with tampico and coir fibre as the reinforcement agents using a bi-axial rotomoulding machine. NaOH-treated fibres with 5, 10 and 15% by weight have been added to the linear low density polyethylene matrix, and the composites were prepared by rotational moulding process. Mechanical properties such as tensile strength, flexural strength, impact strength and hardness have been investigated. Dynamic mechanical behaviour such as storage modulus, loss modulus and tan δ of the different composites has been investigated with dynamic mechanical analyser. Fractured surfaces were examined qualitatively with the help of a scanning electron microscope for determining the interfacial properties and fibre adhesion between the fibres and the linear low density polyethylene matrix.